PENGARUH JENIS DAN CARA APLIKASI BAHAN ORGANIK TERHADAP HASIL PADI (ORYZA SATIVA L.) DI MEDIA TANAM GAMBUT - Hapsoh Hapsoh; Isna Rahma Dini; Wawan Wawan; David Panusunan Natanael (Jurnal Solum, 2021)
This study aims to determine the types and ways of application of organic matter and the combination of both of the rice yields in peat growing media. This research has been carried out in the Experimental Garden of the Faculty of Agric ulture, Riau University, Campus Bina Widya Km 12.5, Simpang Baru Panam Sub-District, Tampan District, Pekanbaru, Riau. This research was carried out for 4 months, starting from May to August 2018. The research was conducted experimentally arranged according to a completely randomized design (CRD) factorial pattern consisting of 2 factors. Factor I: organic matter of plant waste (O), namely: O1 (125 g rice straw), O2 (125 g soybean litter), O3 (oil palm empty fruit bunches 125 g) and Fact II: how to apply organic material (C), namely: C1 (mixed) and C2 (spread). The results obtained were analyzed using variance analysis and continued with the double range duncan's new multiple range test (DNMRT) at 5% level. However, the type of organic rice paddy yields results in the weight of the milled dry grain which is 106.94 g-138.23 g, the weight of 1,000 grains that is 26.40 g-26.95 g and soybean litter on the percentage of rice grain grain 86.24 g-88.00 g. Giving application method in the distribution gives results on the weight of dry milled unhulled rice that is 125.21 g-126.02 g, the weight of 1,000 grains that is 26.65 g-26.79 g and the percentage of unhulled grain that is 86.76 g-87 , 74 g and the combination of the type of organic rice paddy and the application method in the distribution gives the results of the weight of the milled dry rice which is 102.94 g - 140.87 g, the weight of 1,000 items, which is between 26.29 g - 27.27 g and soybean litter organic material types and application method are mixed namely 84.94 g - 88.50 g.Key words : application method, rice plant, rice straw, soybean litter, TKKS.